EFL Pre-Service Teachers' Experiences in Speaking through a Digital Storytelling Project - Risdayani, Nadila; Limbong, Effendi; Sunggingwati, Dyah (Universitas Negeri Gorontalo, 2024)
This study delves into the experiences of EFL pre-service teachers engaging in a digital storytelling project to practice their speaking, with a focus on exploring significant learning outcomes through Fink's 2003 theory. This qualitative case study utilized semi-structured interviews and project reports as instruments, collecting data from five EFL pre-service teachers at Mulawarman University Samarinda through purposeful sampling. Thematic analysis was employed to analyze the data. Four major themes emerged from the data's thematic analysis, which encompassed the experiences of the participants: participation in the process of creating digital stories, focused speaking exercises, integration of other language abilities, and self-evaluation techniques. These themes also brought attention to the participants' learnings about digital storytelling for public speaking, the difficulties they faced, and the spectrum of emotions they went through. Furthermore, the significant learning outcomes they experienced were marked by an improvement in speaking skills and the establishment of speaking habits. Participants also gained insight into the relationship between activities such as writing scripts, recording, and reading for text reviews, all of which contributed to practicing their speaking. This project fosters self-awareness, enhances understanding of others, and instils an interest in undertaking similar projects in the future. Demonstrated ongoing learning highlights the impact of digital storytelling beyond technical skills, serving as a valuable tool for speaking practice.